2003
DOI: 10.1002/cjg2.354
|View full text |Cite
|
Sign up to set email alerts
|

Directional Characteristics of Resistivity Changes in Rock of Original Resistivity Anisotropy

Abstract: According to pre-designed patterns, multiple electrodes are arranged on the surfaces of four samples. Among them three samples have the original resistivity anisotropy which was not formed by ingredient of rock and one sample has that formed by ingredient of rock. The samples are fully saturated with water. The multiple electrodes are combined form arrays of resistivity changing anisotropy in different directions and spacing. The experiments of dynamic rock resistivity change are done with uniaxial compression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…For example, Mao et al [7,8] used the resistivity data measured along E-W and N-S trending measuring lines in studying the changes in the degree of earth resistivity anisotropy during the course of earthquake preparation. Chen et al [22][23][24][25] designed four measuring lines in studying the changes of apparent resistivity anisotropy in lab. In this paper, we arranged three measuring lines intersecting at point O (Figure 1), which allowed us to study the changes in apparent resistivity anisotropy at point O with pressure and depth.…”
Section: Apparent Resistivity Anisotropymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Mao et al [7,8] used the resistivity data measured along E-W and N-S trending measuring lines in studying the changes in the degree of earth resistivity anisotropy during the course of earthquake preparation. Chen et al [22][23][24][25] designed four measuring lines in studying the changes of apparent resistivity anisotropy in lab. In this paper, we arranged three measuring lines intersecting at point O (Figure 1), which allowed us to study the changes in apparent resistivity anisotropy at point O with pressure and depth.…”
Section: Apparent Resistivity Anisotropymentioning
confidence: 99%
“…The striking changes in electrical resistivity and its anisotropy were widely observed before earthquake, mine earthquake, volcanic activities, and geologic motions [1][2][3][4][5][6][7][8][9][10][11][12]. In order to address the change characteristics of resistivity and its anisotropy, many investigators conducted a plenty of experiments on rock samples under compression and during fracture, shear, and frictional sliding in lab [13][14][15][16][17][18][19][20][21][22][23][24][25] and theoretic studies [26][27][28][29][30]. Experimental results reported by Brace et al [13] and Brace and Orange [14][15][16] in lab showed that striking changes in electrical resistivity were observed for a variety of igneous and sedimentary crystalline rocks when water-saturated crystalline rocks were stressed to fracture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the studies of Chen et al [ 12 ], Chen et al [ 15 , 16 , 17 , 18 ] gradually developed and improved the method of determining the main rupture direction of rock by using the anisotropy of the changes of the rock electrical resistivity. They performed a series of experimental studies on the anisotropy of the electrical resistivity of rock samples in uniaxial, low-confining-pressure triaxial and shear conditions by means of combined measurement of the anisotropy of the apparent resistivity, electrical profiling and electrical sounding.…”
Section: Introductionmentioning
confidence: 99%
“…apparent resistivity of rock during the loading process was widely studied (Chen et al, 1987;Mao et al, 1988;Chen et al, 2003;Liao et al, 2003 analyzed the relationship between the anisotropy of the variation of dynamic rock resistivity and the change of water network conductive path caused by the extension of rock fracture through laboratory experiments, and then proposed a quantitative method of identifying the extending premonition of hidden fracture; the variation of the resistivity of water-saturated rock under uniaxial compression was studied (Brace, 1975), and the results showed that under 1/3 to 2/3 of the burst pressure during the loading process, the resistivity of saturated rock initially increased and then decreased rapidly.…”
mentioning
confidence: 99%